2020
DOI: 10.1042/bst20190223
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BMP signaling in the bone marrow microenvironment of myeloid leukemia

Abstract: The bone morphogenetic protein (BMP) pathway regulates the fate and proliferation of normal hematopoietic stem cells (HSC) as well as interactions with their niche. While BMP2 and BMP4 promote HSC differentiation, only BMP4 maintains HSC pool and favors interactions with their niche. In myeloid leukemia, we have identified intrinsic and extrinsic dysregulations of the BMP pathway in Chronic Myeloid Leukemia (CML) and Acute Myeloid leukemia (AML) responsible for leukemic stem cells (LSC) survival. In AML, BMP p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Indeed, inhibition of BMP signaling leads to CSC death, and interrupts BMP production by surrounding stromal cells, in cooperation with other current treatments which remain inefficient as monotherapies (Jeanpierre et al, 2021). This proof-of-concept established in the hematopoietic system is likely to be extended to other cancers (Jung et al, 2019;Lefort and Maguer-Satta, 2020). Collectively, data imply a major role for the BMP pathway in orchestrating the dynamics of the CSC niche ecosystem in different cancers and at all stages of tumor progression.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, inhibition of BMP signaling leads to CSC death, and interrupts BMP production by surrounding stromal cells, in cooperation with other current treatments which remain inefficient as monotherapies (Jeanpierre et al, 2021). This proof-of-concept established in the hematopoietic system is likely to be extended to other cancers (Jung et al, 2019;Lefort and Maguer-Satta, 2020). Collectively, data imply a major role for the BMP pathway in orchestrating the dynamics of the CSC niche ecosystem in different cancers and at all stages of tumor progression.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to intrinsic regulation, extrinsic regulation of the bone marrow microenvironment plays an important role in CML progression ( Kumar et al, 2020 ; Lefort and Maguer-Satta, 2020 ). Based on the findings of circulating lncRNAs, including H19 expression, we targeted the exosome compartment to investigate the potential regulatory role of LNC000093.…”
Section: Resultsmentioning
confidence: 99%
“…One study examined their role in chondrocyte proliferation and found that the deletion of BMP-2 gene alone resulted in severe chondrodysplasia while the deletion of BMP-4 led to a minor cartilage phenotype. 54 Likewise, in acute myeloid leukemia, a distinct role of BMP-4 versus BMP-2 has been evidenced: 55,56 BMP-4 solely is involved as it activates a specific signaling pathway promoting immature resistant leukemic cells, which eventually leads to a relapse after treatment. 55,56 In view of our findings regarding the specific differences between BMP-2 and BMP-4, it will be interesting to further evaluate their specific functions in different cell signaling contexts.…”
Section: Discussionmentioning
confidence: 99%